MODEL PEMBELAJARAN FIQIH BERBASIS TEORI BELAJAR MODERN - Rika Riauwati; Chanifudin (STAI Nurul Falah Airmolek, 2026)
The development of 21st-century education requires a reorientation of learning models, including in Fiqh instruction within Islamic education. In practice, Fiqh learning is still dominated by traditional approaches that emphasize memorization and lectures, resulting in low student engagement and limited meaningful understanding. This study aims to formulate a Fiqh learning model based on the integration of modern learning theories, namely liberal learning, cognitive constructivism, social constructivism, and contextual learning. Using a qualitative approach with a library research method, this study analyzes and synthesizes relevant literature from books and scholarly journals related to learning theories, Fiqh education, and Islamic pedagogy. The findings indicate that integrating Cooperative Learning, Problem-Based Learning, and Contextual Teaching and Learning within a modern theoretical framework can enhance students’ active participation, critical thinking, social interaction, and contextual understanding of Fiqh concepts. This integrative model contributes theoretically to the development of holistic Fiqh pedagogy and practically offers guidance for educators to design more relevant and meaningful learning experiences in contemporary Islamic education.